2021
DOI: 10.1186/s12885-021-07784-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined prognostic value of the SUVmax derived from FDG-PET and the lymphocyte-monocyte ratio in patients with stage IIIB-IV non-small cell lung cancer receiving chemotherapy

Abstract: Background We evaluated the prognostic potential of tumor 18F-fluorodeoxyglucose (FDG) uptake derived from positron emission tomography (PET) and known inflammatory hematological markers, both individually and in combination, for chemosensitivity and survival in patients with stage IIIB-IV non-small cell lung cancer (NSCLC) receiving first-line chemotherapy. Methods A total of 149 patients with stage IIIB and IV NSCLC (based on TNM 7th edition) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, clinical studies have reported that patients with lung cancer had high levels of neutrophils in both the tumor and the circulation (26)(27)(28). The higher neutrophil/lymphocyte ratios were associated with higher recurrence rates following operations, less effective treatment responses and worse prognoses compared with the lower ratios (29)(30)(31)(32).…”
Section: Tansmentioning
confidence: 99%
“…Furthermore, clinical studies have reported that patients with lung cancer had high levels of neutrophils in both the tumor and the circulation (26)(27)(28). The higher neutrophil/lymphocyte ratios were associated with higher recurrence rates following operations, less effective treatment responses and worse prognoses compared with the lower ratios (29)(30)(31)(32).…”
Section: Tansmentioning
confidence: 99%
“…In one study of head and neck cancer, NLR was positively correlated with FDG-PET metabolic markers, including SUV max [ 39 ]. In NSCLC, LMR and NLR showed a weak significant correlation with SUV max [ 15 ]. In another study, SUV max and LMR were independent prognostic factors in patients with stage IIIB-IV NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…FDG-PET parameters are tumor glucose metabolic markers. Typically, the maximum standardized uptake value (SUV max ) has been associated with the progression, metastasis, and prognosis of various cancer types, including lung cancer [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 18 F-FDG PET/CT has been proven to be effective for diagnosing, staging, prognosis prediction, and treatment response assessment in numerous cancers. Conventional metabolic parameters, including metabolic tumor volume (MTV), total lesion glycolysis (TLG), and maximum and peak standardized uptake value (SUVmax/SUVpeak), have been proven to be effective for predicting the survival outcomes of cancer patients [ 7 9 ]. The concept of intratumor metabolic heterogeneity poses a challenge to patients' molecular stratification and treatment guidelines using a single tumor tissue sample [ 10 ].…”
Section: Introductionmentioning
confidence: 99%